Dynamic modelling of the demand for money in Latvia - Boriss Siliverstovs (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
This study develops a parsimonious stable coefficient money demand model for Latvia for the period from 1996 till 2005. A single cointegrating vector between the real money balances, the gross domestic product, the long-term interest rate, and the rate of inflation is found. Our study contributes to better understanding of the factors shaping the demand for money in the new Member States of the European Union that committed themselves to adopting of the Euro currency in the near future.
Keywords: C32; E41; 330; M2 money demand; stability; new EU member states; Latvia; Geldnachfrage; Geldmenge; Kointegration; Lettland